STRATEGY FOR DEVELOPMENT OF RANSANG BARAT FISHERMAN COMMUNITY WITH THE PERSPECTIVE OF HDI INDICATORS - Ramadona Tomi; Darwis Darwis (Berkala Perikanan Terubuk, 2022)
The development program aims to improve the quality of life of the community. One form of measuring the quality of human resources is the Human Development Index (HDI). This indicator also applies to fishermen communities. HDI is an important indicator to measure and plan the success of developing the quality of life of fishermen communities. This research was conducted from May to August 2021 in Ransang Barat District. This study uses a quantitative descriptive approach with a survey method. Sampling was carried out by accident methode on 30 fishermen scattered on the coast of Ransang Barat District. The data analysis technique in determining the HDI value is the calculation based on the geometric mean of the health index, knowledge index and expenditure index which refers to the UNDP calculation model. Based on the results of the analysis, the HDI value of the Ransang Barat fishermen community was 57.07. These values can be broken down based on 3 aspects that make up the HDI as follows: Health index 71.67; Education index 66.83; and the Expenditure index of 39.78. The value of the health index is indicated by the child mortality rate which is influenced by public access to health facilities. The low education index is caused by the limited economic and physical access of the community to basic education facilities. The expenditure index value is influenced by low productivity which causes low income and affects the limited ability of the community to access the necessities of life. Based on the AHP analysis, it is found that the fishing community development policies with an HDI perspective are prioritized to increase access to capital and fishery production inputs (priority 1) and the development of alternative livelihoods (priority 2).